(untitled) (Islamic Sciences Journal, 2023)
This research was in “Al-Aqili’s saying is more like in his book Al-Du’afa”, I made a brief definition of Imam Al-Aqili, and his book Al-Da’afa, then I collected hadiths in which Al-Aqili explained the difference between its narrators, and favored one of its aspects by saying “more like it.” Then a study of the one on whom the dispute revolved, and then I compared Al-Aqili’s saying with the critics who spoke with him in the hadith to reach the most correct opinion, extracting the clues that he relied on in his recommendations, and I concluded it with the most important results that I reached through this research.